HOTEL SERVICE ON VEHICLES IN TOURIST SERVICES: GENERAL PRINCIPLES AND DIRECTIONS OF RESEARCH - Horb, K. M.; Korneyev, M. V.; Nebaba, N. O.; Saihak, Ye. L. (Systems and Technologies, 2026)
The article is devoted to systematizing information on the application of the basic principles and procedures of hotel ser- vice on vehicles, mainly during their movement within the framework of a tourist trip, with the aim, first of all, of further improv- ing the system of standardization and certification of tourist transportation and accommodation services and their combinations. The organization of overnight stays on vehicles during their movement in many cases requires the application of the principles, methods and technologies of the hotel industry and hotel service. The authors have identified various areas of combination and connection of hotel and transport services in the process of servicing tourists during travel – hotels at hubs, common booking procedures, transport service of classic hotel enterprises, stationary hotels in former mobile vehicles, and the presence of hotel service of various levels of manifestation and specific- ity on vehicles during long and long-distance transportation of tourists. The latter area determines the differentiation of the depth of application of hotel technologies on mobile vehicles depending on the duration of the trip, their design and technical characteristics. The above circumstances allowed the authors to identify five levels of hotel support for long-distance tourist transport – from providing minimal service to improve the comfort and convenience of overnight stays in seats in conditions of limited interior space (classic tourist buses) to a full-fledged diversified service-production mobile hotel complex with the widest range of basic, additional and related services (large multi-deck cruise liners). At the last level, all organizational, managerial, technical and technological components, rules and principles of classic hotel management are used particularly vividly and fully, including laundry, elevator, cleaning and other typical hotel services. The use of this five-level model will allow in further developments to include vehicles, during the movement of which hotel service is most clearly manifested when providing tourist travel, to important components in the system of hotel organization, to take them into account in the formation of national and other standards of hotel service, which is of great importance for improv- ing the quality of services and competitiveness of enterprises in the tourism, transport and hotel business.